The Contribution of Capital Assistance Promotional Strategies and Organizational Capability to Micro Business Performance in the New Normal Era - Handayani, Christina Menuk Sri; Suharyanto, Suharyanto; Wibowo, Tony Susilo; Dolah, Rahayu binti Haji (LP2M INSURI Ponorogo, 2023)
This research was conducted to determine the contribution of capital assistance, promotional strategies, and organizational skills to micro-businesses performance in the new normal era. This research is applied to micro-enterprises in Surabaya that must face the environmental conditions after the Covid-19 Pandemic, namely the new normal where there are changes in behavior by the community and micro-businesses related to the pandemic that has occurred, starting new businesses with various uncertainties, high-intensity competition. The Surabaya city government has used different methods to overcome the micro-enterprise downturn by providing trading opportunities and holding grand events to promote products and provide financial assistance. The population of this research is micro-entrepreneurs in Surabaya, totaling 112 people. The survey method is used to retrieve the necessary data from the sample. Testing with multiple linear regression shows the contribution of the variable capital assistance, promotion strategy, and organizational ability to business performance shows that micro-business performance is influenced by capital assistance, promotion strategy, and organizational capacity. The capital assistance obtained is used to carry out product innovations, promotion innovations, distribution, and additional resources supported by organizational capabilities that can improve micro-business performance.